Monitoring of Heart Rhythm Changes After Myocardial Infarction According to the Data of Heart Echocardiography in Outpatient Conditions - Madjidova G.T.; Sunnatova G.I; Mardiev Alimardon (Genius Journals, 2023)
Myocardial infarction is one of the most important socio-economic problems in the world due to high mortality and disability of the population. Patients who have had myocardial infarction are at increased risk, their life expectancy is half as long, and the incidence of cardiovascular complications and death is significantly higher than in people of the same age without myocardial infarction. The study included 45 men aged 40 to 60 years (49.2±2.5 years) who were admitted to the cardio intensive care unit with a diagnosis of ACS with further transformation into AMI with a Q wave (20 bx) or without a Q wave (20 b -X). The control group consisted of 35 practically healthy men aged 35 to 60 years (47.9±2.5 years). Upon admission to the hospital, patients received standard therapy: for ACS without ST segment elevation - antiplatelet agents (aspirin), anticoagulants (heparin), beta-blockers, ACE inhibitors, nitrates, potassium preparations. In ACS with ST segment elevation, patients underwent thrombolytic therapy for 6 hours , in addition to the generally accepted standard therapy
Keywords: myocardial infarction; chronic heart failure; coronary heart disease; acute heart failure